Automated measurement of syntactic complexity in corpus-based L2 writing research and implications for writing assessment. (October 2017) - Lu, Xiaofei
Research investigating corpora of English learners' language raises new questions about how syntactic complexity is defined theoretically and operationally for second language (L2) writing assessment. I show that syntactic complexity is important in construct definitions and L2 writing rating scales as well as in L2 writing research. I describe the operationalizations of syntactic complexity measurement in corpus-based L2 writing research, focusing on the Biber Tagger (Biber, Johansson, Leech, Conrad, & Finegan, 1999), Coh-Metrix (McNamara, Graesser, McCarthy, & Cai, 2014), and L2 Syntactic Complexity Analyzer (Lu, 2010), which are three tools commonly used to automate syntactic complexity analysis. A review of findings from recent corpus-based L2 writing studies on the relationship of syntactic complexity to L2 writing quality follows. I conclude with a discussion of the implications of these multiple perspectives on the definition of syntactic complexity in L2 studies.